Equity Compensation Incentive in Syariah Stock Companies in Indonesia: The Role of Executive Factors and Companies - Muhammad Zulham Tarmuzi Maradjabesi; Ari Warokka; Faizul Mubarok (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the effect of executive factors, including executive overconfidence, average age of executives, and tenure of executives, as well as company factors such as growth, return on total assets, and market ratio, on equity compensation incentives. The study focuses on sharia-compliant companies listed on the Indonesia Stock Exchange. Utilizing secondary data sourced from the official websites of the Financial Services Authority and Bank Indonesia, this study covers a ten-year period from 2010 to 2020. Using panel data analysis through E-views software, this study seeks to provide valuable insights into the dynamics of executive and company factors that influence equity compensation incentives in the context of sharia-compliant companies in Indonesia. The results show that executive overconfidence, average age of executives, and tenure of executives positively affect equity compensation incentives. The higher the level of executive confidence, age, and experience, the higher the likelihood of receiving equity compensation incentives. In addition, growth, ROA, and market ratio also positively affect equity compensation incentives, highlighting the alignment of executive incentives with strong financial performance and the company's strategic growth.